Endogenous Hormones Inhibit Differentiation of Young Ears in Maize (Zea mays L.) Under Heat Stress - Wang, Hui-Qin; Liu, Peng; Zhang, Ji-Wang; Zhao, Bin; Ren, Bai-Zhao (Frontiers in Plant Science, 2020)
Global warming frequently leads to weather with extreme temperatures, which poses a serious threat to crop growth and development. The growth and yield formation of maize are also adversely affected. For the experiment reported in this paper, which aimed to deeply explore the molecular mechanism of ear development under heat stress, we selected the heat-resistant maize variety ZD958 (Zhengdan 958) and the heat-sensitive maize variety XY335 (Xianyu 335), and subjected them to heat stress in the V9 (9th leaf), V12 (12th leaf) and VT (tasseling) growth stages. Through analyzing the maize phenotype, and combining it with omics technology and physiological indicators, we compared the differences in ear morphology, the total number of florets, the floret fertilization rate, the number of grains, the grain abortion rate, and the main metabolic pathways between the plants subjected to heat stress and those left to develop normally. The results showed that after heat stress, the length and diameter of young ears, the total number of florets, the floret fertilization rate, and the number of grains were decreased significantly, whereas the length of the undeveloped part at the top of the ear and the grain abortion rate were increased significantly. In addition to this, the DEGs (differentially expressed genes) in young ears were significantly enriched in the hormone signaling pathways. The endogenous hormones content in young ears exhibited different changes: ZT (zeatin) and ZR (zeatin riboside) were significantly decreased, but GA4 (gibberellin acid4) and ABA (abscisic acid) were significantly increased in ears subjected to heat stress. For the heat-resistant maize variety, the SA (salicylic acid) and JA (jasmonic acid) content in the vegetative growth stage was also increased in ears subjected to heat stress, whereas the opposite effect was observed for the heat-sensitive variety. The changes in the endogenous hormone content of young ears that were subjected to heat stress significantly affected ear development, resulting in reduced the numbers of differentiated florets, fertilized florets and grains, which ultimately reduced the maize yield.